Makna Komunikasi Interpersonal dalam Film Keluarga Cemara - Donny Ibrahim Alsa; Ikeu Junita Triwardhani (Bandung Conference Series: Communication Management, 2022)
Abstract. Films are a form of mass media that not only provide entertainment functions, but can also provide educational and information functions for the audience. This study uses a qualitative research method with a semiotic approach. The object of this research is the film "Keluarga Cemara". Film Keluarga Cemara is a family film that tells the story of the simple life of the four characters, Abah, Emak, Euis and also Ara. In this film there are many positive values that can be taken by the audience, such as how to be a good listener, learn to be grateful, and also be able to see how interpersonal communication in the family can be effectively established. This research will examine the interpersonal communication contained in the film Keluarga Cemara. This study uses the semiotic theory proposed by Roland Barthes. By using Roland Barthes' semiotic theory, this research will examine the denotative, connotative and mythical interpersonal communication contained in the film Keluarga Cemara. Based on the results of the observations that the researchers conducted on the film Keluarga Cemara, the researcher found that the denotative meaning of interpersonal communication in the Cemara family film was depicted using verbal and nonverbal communication, while the connotative meaning of interpersonal communication in the Cemara family film was depicted in the form of communication effectiveness, namely in the form of openness, empathy, attitude. supportive, positive attitude and equality. And on the meaning of the myth of interpersonal communication in the film family cemara which is tried to be lifted by showing how the situation of a harmonious family is even with the situation not wallowing in wealth. Abstrak. Film merupakan salah satu bentuk media massa yang tidak hanya memberikan fungsi hiburan, namun juga dapat memberikan fungsi edukasi dan informasi bagi para penontonnya. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan semiotika. Objek dalam penelitian ini adalah film “Keluarga Cemara”. Film Keluarga Cemara adalah sebuah film keluarga yang bercerita mengenai kehidupan sederhana keempat tokohnya, Abah, Emak, Euis dan juga Ara. Dalam film ini terdapat banyak nilai positif yang dapat diambil oleh penontonnya, seperti bagaimana menjadi pendengar yang baik, belajar bersyukur, dan juga dapat melihat bagaimana komunikasi antarpribadi dalam keluarga dapat terjalin dengan efektif. Penelitian ini akan meneliti mengenai komunikasi antarpribadi yang terkandung dalam film Keluarga Cemara. Penelitian ini menggunakan teori semiotika yang diusung oleh Roland Barthes. Dengan menggunakan teori semiotika Roland Barthes maka penelitian ini akan mengkaji mengenai denotatif, konotatif dan mitos komunikasi antarpribadi yang terkandung dalam film Keluarga Cemara. Berdasarkan hasil obervasi yang peneliti lakukan terhadap film Keluarga Cemara, peneliti menemukan bahwa makna denotative komunikasi interpersonal dalam film keluarga cemara digambarkan menggunakan komunikasi verbal dan nonverbal, adapun makna konotatif komunikasi interpersonal dalam film keluarga cemara digambarkan dalam bentuk efektivitas komunikasinya yaitu berupa keterbukaan, empati, sikap mendukung, sikap positif dan kesetaraan. Dan pada makna mitos komunikasi interpersonal dalam film keluarga cemara yang coba diangkat dengan menunjukan bagaimana keadaan dari keluarga yang harmonis meski dengan keadaan tidak bergelimang harta.